A compact ultra wideband antenna with WLAN (IEEE 802.11a) band rejection - Jalil Y.E.; Chakrabarty C.K.; Kasi B. (2023)
The problem of interference between ultra-wideband (UWB) system and other narrow band systems has been a major concern for a long time. This paper presents a compact UWB antenna that shows desirable band-notch and gain characteristics. The proposed antenna consists of an octagon-shaped patch with a truncated ground plane that is fed by a 50? microstrip line. The frequency notch characteristic is obtained by inserting two C-shape slots on the radiating patch. The proposed antenna is successfully designed and simulated showing good impedance matching and reasonable radiation patterns over a bandwidth of 2.8 to 11 GHz. Furthermore, the proposed antenna has a compact size of 26 32 mm2 while exhibiting the band rejection performance in the frequency band of 5.15 to 5.85 GHz. 2012 IEEE.